The association between the neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and monocyte-to-lymphocyte ratio and systemic sclerosis and its complications: a systematic review and meta-analysis - Zinellu, Angelo; Mangoni, Arduino A. (Frontiers in Immunology, 2024)
The identification of new, easily measurable biomarkers might assist clinicians in diagnosing and managing systemic sclerosis (SSc). Although the full blood count is routinely assessed in the evaluation of SSc, the diagnostic utility of specific cell-derived inflammatory indices, i.e., neutrophilto-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and monocyte-to-lymphocyte ratio (MLR), has not been critically appraised in this patient group. We conducted a systematic review and meta-analysis of studies investigating the NLR, PLR, and MLR, in SSc patients and healthy controls and in SSc patients with and without relevant complications. PubMed, Scopus, and Web of Science were searched from inception to 23 February 2024. Risk of bias and certainty of evidence were assessed using validated tools. In 10 eligible studies, compared to controls, patients with SSc had significantly higher NLR (standard mean difference, SMD=0.68, 95% CI 0.46 to 0.91, p˂0.001; I 2 =74.5%, p<0.001), and PLR values (SMD=0.52, 95% CI 0.21 to 0.83, p=0.001; I 2 =77.0%, p=0.005), and a trend towards higher MLR values (SMD=0.60, 95% CI -0.04 to 1.23, p=0.066; I 2 =94.1%, p˂0.001). When compared to SSc patients without complications, the NLR was significantly higher in SSc with interstitial lung disease (ILD, SMD=0.31, 95% CI 0.15 to 0.46, p˂0.001; I 2 =43.9%, p=0.11), pulmonary arterial hypertension (PAH, SMD=1.59, 95% CI 0.04 to 3.1, p=0.045; I 2 =87.6%, p<0.001), and digital ulcers (DU, SMD=0.43, 95% CI 0.13 to 0.74, p=0.006; I 2 =0.0%, p=0.49). The PLR was significantly higher in SSc patients with ILD (SMD=0.42, 95% CI 0.25 to 0.59, p˂0.001; I 2 =24.8%, p=0.26). The MLR was significantly higher in SSc patients with PAH (SMD=0.63, 95% CI 0.17 to 1.08, p=0.007; I 2 =66.0%, p=0.086), and there was a trend towards a higher MLR in SSc patients with ILD (SMD=0.60, 95% CI -0.04 to 1.23, p=0.066; I 2 =94.1%, p˂0.001). Pending the results of appropriately designed prospective studies, the results of this systematic review and meta-analysis suggest that blood cell-derived indices of inflammation, particularly the NLR and PLR, may be useful in the diagnosis of SSc and specific complications. (PROSPERO registration number: CRDCRD42024520040).